Pengaruh Harga Dan Fasilitas Terhadap Keputusan Konsumen Menginap Di Losmen Simpang Lahat - Via Rindani Mahesa; Hayani Hayani; Iskandar Iskandar (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to determine the Influence of Price and Facilities on Consumers' Decisions to Stay at Simpang Lahat Inns either partially or simultaneously. This study is a quantitative associative research using the Accidental Sampling technique with the slovin formula method in determining samples. The sample used in this study amounted to 84 research respondents. Based on the results of the study, the regression equation Y = 4.494 + 0.421 X1 + 0.467 X2 + e, means that without the variables Price (X1) and Facilities (X2), the Stay Decision (Y) is 4.494. The value of the determination coefficient (R2) is 0.551, meaning that the independent variables have a contribution with dependent variables of 55.1% and the remaining 44.9% are influenced by other factors that were not studied by the author. Based on the results of SPSS processing version 25.0, the Fcal value of 49.638 was obtained while the Ftable value was 3.109 thus 49.638 > 3.109, then Ho was rejected and Ha was accepted, meaning that the variables Price (X1) and Facilities (X2) together had a significant effect on the Stay Decision (Y). The Ttable value is 1.664. By comparing the values of Thcal and Ttabel it can be concluded: the variable Price (X1) with the value of Thcal > Ttable or 5.092 > 1.664 then Ho is rejected and Ha is accepted. Facilities (X2) with a Thcal value of > Ttable or 5.739 > 1.664, then the variables Price (X1) and Facilities (X2) have a partial effect on the Decision to Stay (Y) at the Simpang Lahat Inn.